2022
DOI: 10.1177/07334648221132121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Medicaid Expansion on Health Insurance for Low-Income Nursing Home Aides

Abstract: We examine how the Affordable Care Act Medicaid expansion affected the insurance coverage and the sources of coverage among low-income nursing home aides using the 2010–2019 American Community Survey data. Insurance coverage for low-income nursing home aides increased from about 60% to nearly 90% in expansion states but rose to only about 80% in nonexpansion states. Using a difference-in-differences regression design, we find that Medicaid expansion was associated with a 5.1 percentage-point increase in overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
3
1
Order By: Relevance
“…30 A number of studies have now documented crowd-out of private insurance by Medicaid among lowincome populations. 31,32,52 While we do not observe similar trends in non-expansion states, private insurance remains to be the largest coverage option for low-income people in those regions. In light of our null findings with regard to underinsurance, this may suggest that the expansion of Medicaid may not be the sole factor influencing underinsurance rates.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…30 A number of studies have now documented crowd-out of private insurance by Medicaid among lowincome populations. 31,32,52 While we do not observe similar trends in non-expansion states, private insurance remains to be the largest coverage option for low-income people in those regions. In light of our null findings with regard to underinsurance, this may suggest that the expansion of Medicaid may not be the sole factor influencing underinsurance rates.…”
Section: Discussioncontrasting
confidence: 77%
“…Even though increased demand is expected, most of the bill is to be covered by the government in this case. Other insurance dynamics such as the “crowd-out” of private insurance with Medicaid 30 - 32 or individuals switching from employer-provided to subsidized insurance 33 may have led to improved coverage with potentially lower deductibles and copayments. Hence, it is plausible to foresee reduced out-of-pocket expenditures among Medicaid enrollees and decreased probability of criterion-specific underinsurance among low-income individuals in expansion states.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Studies have documented an increase in health coverage and provided evidence for improvement in access and health status following the ACA, including research examining both Medicaid and non-Medicaid provisions (Barbaresco et al, 2015; Charles Courtemanche, Marton, Ukert, Yelowitz, & Zapata, 2017a, 2017b; Courtemanche et al, 2016, 2018, 2019, 2020) or focusing on the Medicaid expansions (Bin Abdul Baten & Wehby, 2022a, 2022b; Semprini & Wehby, 2022; Sommers et al, 2016; Wehby & Lyu, 2018; Wherry & Miller, 2016; Xu & Sharma, 2023). Most of these studies, however, do not focus on the 50–64 age range.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence regarding the impact of Medicaid expansion on private insurance is mixed and largely dependent on the specific context in which the expansion is implemented (Atherly et al., 2016; Dong, Gindling, and Miller, 2022; Dubay and Kenney, 2001; Ellis and Esson, 2021; Lindner, Levy, and Horner‐Johnson, 2021; Marquis and Long, 2003; McInerney et al., 2020; Wagner, 2015; Xu and Sharma, 2023; Yazici and Kaestner, 2000). Some studies have suggested that Medicaid expansion has led to a considerable reduction in the number of individuals with private insurance (Dong, Gindling, and Miller, 2022; Ellis and Esson, 2021; Marquis and Long, 2003; McInerney et al., 2020; Wagner, 2015; Xu and Sharma, 2023). Reducing the number of individuals who purchase private insurance could in turn lead to a reduction in revenue for private insurance companies, which then charge higher premiums, and ultimately causing a downward spiral of private coverage take‐up (McWilliams, 2009; Wray, Khare, and Keyhani, 2021).…”
mentioning
confidence: 99%